Военно-политическая работа: учебное пособие - Кисляк А. А. Андрей Антонович; Поздняков Н. А. Николай Анатольевич; Горев С. А. Станислав Андреевич (Томск, Изд-во ТПУ, 2021)
Заглавие с титульного экрана